Economic Assistance on Culinary Business During Pandemic - Hesti Budiwati (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2021)
During the pandemic that not only hit the world but also in Indonesia, there are lot of businesses that went bankrupt. Many businesses are unable to survive the impact of this pandemic, especially small businesses. Our target partner is a home culinary business namely “Dapur Mumpuni”. In addition to selling food, Dapur Mumpuni is currently able to get creative with its innovative pukis cake during the pandemic. The partner has several weaknesses which are (1) limited partner skills in economic management, (2) no bookkeeping regularly, (3) no separation between household and business finances and (4) weak marketing strategy used, resulting in little profit and business is not well developed because it tends to lose in the competition. This community service activity is expected to create targets in accordance with partner expectations namely (1) increasing the partner skills in running its business economically and sustainable, (2) a simple orderly administration, in the sense of being able to separate household and business finances, (3) selling profit increase of effective activity economically and (4) get financial assistance for additional business capital